Impact of Soft Skills Training on a Catering Company in Vietnam - Le Thanh, Liem (Digital Repository of Theses, 2025)
Many employees express difficulty in communicating with their customers, especially in customer service where there are numerous issues and challenges during service and communication. Providing specific training in soft skills is one way to enhance the communication between employees and their customers. We developed and implemented a soft skills training program for employees, consisting of three teaching modules: (1) Basic Communication (BC); and (2) Teamwork Communication (TC). This study focused on a comprehensive 4-day soft skills training program, including didactic sessions and experiential small group role plays. Employees who participated in the program provided valuable feedback through course evaluations, self-reports, and pre-and post- standardized customer assessments. The results were overwhelmingly positive, with participants reporting substantial increases in self-efficacy in their customer communication abilities across various contexts. Furthermore, there was evidence of significant improvements in empathic skills and the ability to clarify information effectively. Soft skills training is becoming an increasingly important function of HR. It helps organizations, especially in the service sector, enhance human resource capital and compete efficiently in a rapidly changing business environment. Large investments have been made in soft skill training programs for employees, and it is a challenge for the training department to justify its financial investment. Our work demonstrates that implementation of a soft skills training program at a catering company is feasible and acceptable and has a significant impact on participants' behavior and company benefits using Kirkpatrick’s four levels evaluation model, this paper specifically examines (1) the reactions of the employees to the training programs; (2) the level of employee’s learning; and (3) the employee’s transfer of training. A sample of 46 employees who attended the Mina Better Behavior (MBB) was selected through the stratified sampling method. Training feedback questionnaires, pre-and post-tests, learner development plan reports, and behavioral surveys were used to evaluate the effectiveness of the training course.